MBA Theory and Application of Business and Management Principles - Machado, Carolina; Davim, J. Paulo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book focuses on the relevant subjects in the curriculum of an MBA program. Covering many different fields within business, this book is ideal for readers who want to prepare for a Master of Business Administration degree. It provides discussions and exchanges of information on principles, strategies, models, techniques, methodologies and applications in the business area.
Management -- Human resource management -- Financial management -- Marketing management -- Operations management -- Information management -- International management -- Accounting -- International business -- Business law -- Statistics -- Economics -- Culture and organizational behaviour -- Competitive management practice -- Global management -- Organizational development and change -- Strategic management -- Entrepreneurship -- Production engineering -- Production management -- Sustainable management.
Keywords: Industrial Management; Business; Management science; Technology -- Sociological aspects; Industrial Management; Business and Management; Science, Technology and Society